2022
DOI: 10.31083/j.fbl2708228
|View full text |Cite
|
Sign up to set email alerts
|

Using the BMD Approach to Derive Acceptable Daily Intakes of Cannabidiol (CBD) and Tetrahydrocannabinol (THC) Relevant to Electronic Cigarette Liquids

Abstract: Background: In the past 60 years, Cannabis sativa L. has been an object of increasing interest because of the psychotropic effects of some of its constituents. These effects mainly arise from the cannabinoid ∆ 9 -tetrahydrocannabinol (∆ 9 -THC). C. sativa species also synthesize and accumulate the non-psychotropic compound cannabidiol (CBD). Due to their therapeutic potential, both cannabinoids are an object of medical research and drug development. More recently, CBD has received increasing interest as an ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“… 12 , 13 The consideration that EVALI was not caused by cannabinoids but other compounds in the e-cigarette liquids was recently validated by a risk assessment of inhaled CBD and THC, which found that the intake would be typically below thresholds of toxicity. 14 Nevertheless, it was also remarked that the available data for risk assessment of CBD is rather limited. Caution is also advised because CBD products may potentially lead to positive urine drug tests due to significant contamination with THC and other cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 The consideration that EVALI was not caused by cannabinoids but other compounds in the e-cigarette liquids was recently validated by a risk assessment of inhaled CBD and THC, which found that the intake would be typically below thresholds of toxicity. 14 Nevertheless, it was also remarked that the available data for risk assessment of CBD is rather limited. Caution is also advised because CBD products may potentially lead to positive urine drug tests due to significant contamination with THC and other cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Data were screened for suitability for benchmark dose-response modelling according to the criteria of Hindelang et al [10]: (i) a study considered for inclusion had to have administered at least three different doses and a control group receiving vehicle, while dose spacing was not considered relevant, (ii) applied doses had to be administered in mg/kg of body weight, (iii) the number of animals per dose group had to be reported, and (iv) studies reporting concomitant treatment with other drugs or medications were not included.…”
Section: Methodsmentioning
confidence: 99%
“…The data were checked for the suitability of benchmark dose-response modelling according to the criteria of Hindelang et al [10]: (i) a study considered for inclusion in this research had to have administered at least 3 different doses and a control group receiving vehicle, while dose spacing was not considered relevant, (ii) applied doses had to be administered in mg/kg of body weight, (iii) the number of animals per dose group had to be declared, and (iv) studies reporting concomitant treatment with other medications were not included.…”
Section: Methodsmentioning
confidence: 99%